CHINA’S CONTROL OVER THE CHINA-PAKISTAN ECONOMIC CORRIDOR: THE PERSPECTIVE OF THE NATIVE PEOPLES OF PAKISTAN - Pradeep; Mishra, Vivek Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Pakistan and China's relationship has always been characterized by political collaboration, economic connections, and as well as military collaboration. These connections have taken on new heights since 2015 when both have concentrated on the China-Pakistan Economic Corridor (CPEC), a group of initiatives that are part of Beijing's Belt and Road Initiative announced in 2013. Pakistan's political leadership refers to the CPEC as a "game changer" that will bring prosperity by revitalizing the fragile economy of the nation. CPEC has been praised as a project that will revolutionize Pakistan's economy and serve as a showcase of China's aspirations for the global economy. However, worries about political influence, economic reliance, and sovereignty have also caused debate within Pakistan. Although the Pakistani government presents the China-Pakistan Economic Corridor (CPEC) as a mutually beneficial development effort, the people of Pakistan are becoming more concerned about China's rising influence over the country's political and economic spheres and started opposition in Balochistan and other provinces. This article looks at how China's influence over the Pakistani government is reflected in the dynamics of the CPEC and analyses the subsequent disagreement and discontent among the Pakistani populace. It also explores how China's Belt and Road Initiative (BRI) ties into the larger geopolitical and economic consequences of CPEC and also concern for India.